2022
DOI: 10.1111/jora.12781
|View full text |Cite
|
Sign up to set email alerts
|

Longitudinal Change in Adolescent Depression and Anxiety Symptoms from before to during the COVID‐19 Pandemic

Abstract: the collection, analysis, and interpretation of data or in writing the manuscript, apart from their financial contribution; the content is solely the responsibility of the authors and does not necessarily represent the official views of any of the funding agencies. We would like to thank Claire Chie for her assistance in reliability coding and all participants and their families for their involvement in the study.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
51
2
3

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 110 publications
(76 citation statements)
references
References 54 publications
7
51
2
3
Order By: Relevance
“…In the KLIK sample for which we have self-reported data, we observed significant increases in mental health problems from before the pandemic to the first measurement during the pandemic (April 2020) on all six mental health domains. In line with previous research, we found the largest increases in anxiety and depression (Barendse et al, 2022; Bignardi et al, 2021; de France et al, 2022). After this initial deterioration the problems stabilized and, in most domains, started to normalize.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the KLIK sample for which we have self-reported data, we observed significant increases in mental health problems from before the pandemic to the first measurement during the pandemic (April 2020) on all six mental health domains. In line with previous research, we found the largest increases in anxiety and depression (Barendse et al, 2022; Bignardi et al, 2021; de France et al, 2022). After this initial deterioration the problems stabilized and, in most domains, started to normalize.…”
Section: Discussionsupporting
confidence: 93%
“…Prospective studies on child mental health during the pandemic that include pre-pandemic measurements are scarce but do seem to confirm that predominantly affective problems such as depressive, anxious, and stress symptoms worsened in the first months after the onset of the COVID-19 pandemic. This seems to be the case for children from the general population (Barendse et al, 2022; Bignardi et al, 2021; de France et al, 2022; Fischer et al, 2022; Luijten, van Muilekom, et al, 2021; van der Velden et al, 2022) as well as for children with pre-existing mental health problems (Breaux et al, 2021; Fischer et al, 2022). On the contrary, some other studies challenge the mental burden of the COVID-19 pandemic in children and report small or no significant differences in mental health problems (Bouter et al, 2022; Burdzovic Andreas & Brunborg, 2021).…”
Section: Introductionmentioning
confidence: 99%
“…We used the Internalizing and Externalizing symptoms subscales from the youth and caregiver report and used the highest reported symptom value across the two reporters as measures of Internalizing and Externalizing symptoms during the pandemic. When compared to recent longitudinal studies and systematic reviews (Barendse et al, 2022;Fegert et al, 2020;Hawes et al, 2021;Racine et al, 2020) the magnitude of symptom increase from before to during the pandemic in the current sample is consistent with that seen in previous work (i.e., 2-3x increase), lending confidence in this approach.…”
Section: Internalizing and Externalizing Psychopathologysupporting
confidence: 89%
“…Over the past two years, much work has focused on the unprecedented challenges the COVID-19 pandemic has created for families (i.e., illness, unemployment) and the associated increase in psychopathology in children and adults (Achterberg et al, 2021;Barendse et al, 2022;Chahal et al, 2020;Ellis et al, 2020;Fegert et al, 2020;Gassman-Pines et al, 2020;Gruber et al, 2020;Hawes et al, 2021;Holman et al, 2020;Loades et al, 2020;Patrick et al, 2020;Pfefferbaum & North, 2020;Pierce et al, 2020;Racine et al, 2020). However, there has been less focus on the impact of the pandemic on the social lives of children and adolescents.…”
Section: Introductionmentioning
confidence: 99%
“…The occurrence rates of these negative emotions were significantly higher than the rates reported for the same emotions before the pandemic ( 55 ). Participants also had significantly lower scores for their levels of physical functioning, social functioning, and school functioning as measured by the PedsQL than the norms for healthy teens ( 71 73 ). These findings further support the notion that the pandemic has been detrimental to young people's mental health and quality of life, worldwide ( 74 77 ).…”
Section: Discussionmentioning
confidence: 86%